Risk Factors And Postoperative Complications In Laparotomy Under General Anesthesia: A Systematic Literature Review - Adelia Trisna Septiani (CV. AFDIFAL MAJU BERKAH, 2026)
Laparotomy is an abdominal surgery procedure that is still widely performed both in elective and emergency conditions. This procedure is often performed under general anesthesia and has a fairly high risk of postoperative complications, such as pulmonary complications, acute kidney injury (AKI), surgical wound infections, ileus, sepsis, and postoperative nausea and vomiting (PONV). The risk of complications may increase due to patient factors, intraoperative factors, and anesthesia factors. This study aims to identify and synthesize risk factors that contribute to postoperative complications in patients undergoing laparotomy surgery under general anesthesia. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach and the PICO framework. Literature searches were conducted on PubMed, ScienceDirect, and Google Scholar databases with a publication range of 2015-2025. The included studies were quantitative studies with a Randomized Controlled Trial (RCT) design and a cohort study that discussed risk factors and postoperative complications in patients undergoing laparotomy surgery or open abdominal surgery under general anesthesia. Article quality assessment was carried out using the Joanna Briggs Institute (JBI) instrument. A total of 4,068 articles were identified in the early stages. After the duplicates were removed, 1,409 articles were obtained for filtering. A total of 238 articles passed the initial screening based on titles and abstracts, then 203 articles were removed because they did not meet the inclusion criteria. A total of 35 articles underwent full-text review, 26 articles were removed because they did not meet the criteria, so that 9 articles were eligible for analysis. The results of the synthesis showed that postoperative complications in laparotomy patients with general anesthesia were multifactorial. Patient factors include advanced age, comorbidities, high ASA status, and poor functional status. Intraoperative factors include hypotension, blood loss, organ perfusion disorders, duration of surgery, and fluid management. Anesthesia factors are primarily related to anesthesia techniques, the use of inhaling agents or TIVAs, and the prevention of PONV. The most commonly reported complications include PPCs, AKI, SSI, sepsis, ileus, and PONV. Postoperative complications in laparotomy surgery with general anesthesia are not caused by a single factor, but rather by an interaction between patient, intraoperative, and anesthesia factors. Preoperative risk assessment, intraoperative hemodynamic monitoring, fluid management based on patient needs, and selection of appropriate anesthesia techniques are necessary to lower the risk of complications and improve patient safety.